Letter from State Fire Marshall, Oklahoma, to Tobacco Institute regarding "Kids Safe Program" (Tufts Archival Research Center, 2007)
Confidential; Letter from Byron Hollander, Oklahoma Fire Marshall to Karen Fernicola, TI, regarding the Oklahoma City Fire Department's "Kid Safe Program." Requests funds from TI to establish fire safety education programs. Explains that "Kid Safe" program targets preschool age children and that money would cover printing cost of curriculum.